Lymphatic Collecting Vessel: New Perspectives on Mechanisms of Contractile Regulation and Potential Lymphatic Contractile Pathways to Target in Obesity and Metabolic Diseases - Lee, Yang; Zawieja, Scott D.; Muthuchamy, Mariappan (Frontiers in Pharmacology, 2022)
Obesity and metabolic syndrome pose a significant risk for developing cardiovascular disease and remain a critical healthcare challenge. Given the lymphatic system's role as a nexus for lipid absorption, immune cell trafficking, interstitial fluid and macromolecule homeostasis maintenance, the impact of obesity and metabolic disease on lymphatic function is a burgeoning field in lymphatic research. Work over the past decade has progressed from the association of an obese phenotype with Prox1 haploinsufficiency and the identification of obesity as a risk factor for lymphedema to consistent findings of lymphatic collecting vessel dysfunction across multiple metabolic disease models and organisms and characterization of obesity-induced lymphedema in the morbidly obese. Critically, recent findings have suggested that restoration of lymphatic function can also ameliorate obesity and insulin resistance, positing lymphatic targeted therapies as relevant pharmacological interventions. There remain, however, significant gaps in our understanding of lymphatic collecting vessel function, particularly the mechanisms that regulate the spontaneous contractile activity required for active lymph propulsion and lymph return in humans. In this article, we will review the current findings on lymphatic architecture and collecting vessel function, including recent advances in the ionic basis of lymphatic muscle contractile activity. We will then discuss lymphatic dysfunction observed with metabolic disruption and potential pathways to target with pharmacological approaches to improve lymphatic collecting vessel function.